Cyberbullying victimization and its influence on Physical Education outcomes among school students - Balnur Balabekovna Kenjayeva; Rustam Bakhtyeruly Abdrakhmanov (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The study addressed the growing concern of cyberbullying among school students and its impact on physical education outcomes, a relationship that remains underexplored in the literature. the topic is particularly relevant given the increasing digital engagement of adolescents and the psychosocial demands of physical education environments.